Challenges and Constraints in Production and Marketing Horticultural Products in Timor Leste - Rola-Rubzen, Maria Fay; Janes, Albert; Correia, Vincente; Dias, F. (International Society of Horticultural Science, 2011)
This paper describes the farming systems in two horticulture growing regions in Timor Leste and outlines the challenges and constraints faced by farmers in the production and marketing of horticultural products. The paper is based on a wider study of farming systems in Timor Leste. One of the main challenges faced by farmers is the low productivity and quality of the produce. This is due to current farm management and post-harvest practices as well as the lack of farm inputs. Product quality is a problem due to poor product handling. Marketing is hampered by the poor transport and road network system, inadequate communication, the lack of storage facilities, and the lack of a grading and standardisation system in the industry. Given the high local demand for vegetables and the potential for exports, it is important to address these challenges for producers to benefit from market oppor-tunities and to increase their incomes. Dealing with these challenges will require a whole value chain approach.